Poly(thymine)-templated copper nanoparticles as a fluorescence probe for highly selective and rapid detection of cysteine. Issue 3 (16th March 2017) - Peng, Jun; Ling, Jian; Tan, Yan-Yan; Jing, Chun-Ju; Li, Xing-Juan; Chen, Li Qiang; Cao, Qiu-E.
ABSTRACT: A highly selective and rapid analytical method was proposed to detect cysteine in aqueous solution by using poly(thymine)-templated copper nanoparticles. In a neutral aqueous condition, the fluorescence of poly(thymine)-templated copper nanoparticles could be quenched by cysteine in 10 min effectively coexisting with common biological small molecules. Under the optimal experimental condition, the present assay allowed for the selective determination of cysteine in the range of 12.5–100 µM, with a detection limit of 7.3 µM. The results indicated that the poly(thymine)-templated copper nanoparticles probe would find potential application in bioanalysis.